Views on Agile Leadership for Software Teams: A Case Study with Leaders and Non-Leaders - Araújo, Narallynne; Massoni, Tiago; Gren, Lucas (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de Software, 2024)
Recent research suggests that agile leadership is regarded as shared, transformational, and dynamic, in the view of technical leaders themselves. Also, it promotes collaboration and a strong sense of belonging, requiring a balance in integrating different organizational cultures. On the other hand, previous research overlooks the perspective of developers who are non-leaders. We conducted a case study involving leaders and non-leaders in two software development teams. The way leaders share leadership activities are similar in terms of technical experience and team tenure but differ in terms of team size, and non-leaders’ aptitude to take on leadership activities. Also, non-leaders’ views on leadership differed from those of leaders; non-leaders considered the leadership they received as individual and hierarchical, in contrast to the leaders’ views, who perceived agile leadership as a shared team attribute. These different points of view provide insights into how the development process can be affected, especially when assigning roles and responsibilities between leaders and non-leaders to achieve agile leadership benefits.